UTILIZING ORAI APPLICATION TO ENHANCE STUDENTS’ ENGLISH SPEAKING PERFORMANCE - Annisa Deliza; Irma Savitri Sadikin (IKIP Siliwangi, 2023)
This study aims to determine how the Orai application could improve students' speaking performance and perceptions of using it as a learning tool. The subject of this study were 40 students of one class of a public senior high school in Tangerang. This particular research is categorized as one group pre-test and post-test experimental design. The data was gathered utilizing three instruments: a pre-test, a post-test, and an interview. The findings revealed that using the Orai application significantly impacts students' speaking abilities. As indicated by the results, using the Orai application could improve students' speaking abilities and perceptions of the Orai app as a learning medium in various areas, including pronunciation, grammatical accuracy, vocabulary, fluency, and interactive communication. The Wilcoxon signed test findings show a difference between the average pre-test and post-test scores after utilizing the Orai application for several treatments, with the value of asymp sig. (2-tailed) 0.000 being smaller than the alpha level of 5% (0.05). These statistics indicate that Orai, an application used to study English, particularly speaking, can help students improve their speaking performance more efficiently. In addition, the use of the Orai application is recommended for teaching instruction since it provides a joyful and engaging learning environment, and stimulated the students' enthusiasm and participation in classroom activities. Keywords: Orai Application; Perception; Speaking